2022
DOI: 10.7150/ijbs.75876
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-6 in Fibrotic Diseases: Molecular and Cellular Mechanisms

Abstract: Fibrosis is a detrimental outcome of most chronic inflammatory disorders and is defined by the buildup of excess extracellular matrix (ECM) components, which eventually leads to organ failure and death. Interleukin 6 (IL-6) is promptly produced by immune cells in response to tissue injuries and has a wide range of effects on cellular processes such as acute responses, hematopoiesis, and immune reactions. Furthermore, high levels of IL-6 have been found in a variety of chronic inflammatory disorders characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 89 publications
1
30
0
1
Order By: Relevance
“…In the PBMCs activation assay, YG-003D3 induced stronger IFN-g, IL-6, and TNF-a secretion compared to that induced by its parental anti-PD-1 or anti-LAG-3 antibodies. Although IL-6 is not the major cytokine secreted by T cells, some literature reports that IL-6 may be secreted by monocytes, macrophages, and dendritic cells (62)(63)(64). Therefore, it can be speculated that YG-003D3 may affect other immune cells, either directly or indirectly, and then induce the expression of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In the PBMCs activation assay, YG-003D3 induced stronger IFN-g, IL-6, and TNF-a secretion compared to that induced by its parental anti-PD-1 or anti-LAG-3 antibodies. Although IL-6 is not the major cytokine secreted by T cells, some literature reports that IL-6 may be secreted by monocytes, macrophages, and dendritic cells (62)(63)(64). Therefore, it can be speculated that YG-003D3 may affect other immune cells, either directly or indirectly, and then induce the expression of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The Immuno‐related procedures used comply with the recommendations made by the British Journal of Pharmacology (Alexander et al, 2018). IL‐6 was measured as it is strongly associated with the onset of fibrosis (Li et al, 2022). Culture medium and perfusate samples were analysed with a Porcine IL‐6 Duo Set enzyme‐linked immunosorbent assay (ELISA) (Bio‐Techne, Abingdon, UK), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Bou‐Gragham's study showed that overexpression of IL‐1α was associated with the worsening of symptoms and disease progression in conditions such as atopic dermatitis, neutrophilic dermatoses, skin phototoxicity, and skin cancer 4 . Similarly, IL‐6 was found to activate TGF‐β, NF‐κB, STAT3, and ERK pathways, while also triggering oxidative stress through the production of reactive oxygen species 5 . In Khan's research, the elevated IL‐6 level was found to correlate with the severity of skin manifestations and the degree of skin thickening, both of which contribute to skin fibrosis—a characteristic feature of systemic sclerosis 6 .…”
Section: Introductionmentioning
confidence: 99%